2002
DOI: 10.1002/aoc.324
|View full text |Cite
|
Sign up to set email alerts
|

Study of in vitro cytotoxicity of arsenocholine, a trimethyl arsenic compound in seafood

Abstract: Study ofWe examined the in vitro cytotoxic effects of an organic arsenic compound contained in seafood, viz. the trimethyl (2-hydroxyethyl)-arsonium cation, or arsenocholine (AsCho), on some murine immune effector cells, such as splenocytes, thymocytes, Peyer's patch lymphocytes, peritoneal macrophages and bone marrow (BM) cells using synthesized pure material. We found that AsCho had no cytotoxicity on most immune effector cells, even at concentrations over 10 mmol dm À3 , and it slightly but significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, it slightly augmented the viability of bone marrow cells (about a 1.3-fold increase in the viability of cells compared with that of control cells during a 72 h incubation) at high concentrations over 100 mmol dm À3 . 33 As described below, this unique biological action was also found to be more effective with AsBe, but was not observed for any other arsenic compounds. 28 Marafante et al 34 and Kaise et al 31 examined the metabolism of AsCho and reported that it was converted to AsBe and rapidly excreted into the urine after oral administration; however, we found that AsCho was not converted into any other arsenicals, including AsBe, in murine bone marrow cells in vitro.…”
Section: à3mentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, it slightly augmented the viability of bone marrow cells (about a 1.3-fold increase in the viability of cells compared with that of control cells during a 72 h incubation) at high concentrations over 100 mmol dm À3 . 33 As described below, this unique biological action was also found to be more effective with AsBe, but was not observed for any other arsenic compounds. 28 Marafante et al 34 and Kaise et al 31 examined the metabolism of AsCho and reported that it was converted to AsBe and rapidly excreted into the urine after oral administration; however, we found that AsCho was not converted into any other arsenicals, including AsBe, in murine bone marrow cells in vitro.…”
Section: à3mentioning
confidence: 83%
“…As described above, the AsBe-induced weak modulating effect on the survival of bone marrow cells was observed with AsCho, which has a chemical structure similar to that of AsBe. 33 Additionally, this biological effect was not observed with any other methyl arsenic compounds, such as monomethylarsonic acid, dimethylarsinic acid 38 and tetramethylarsonium hydroxide. 27 It is very interesting that this unique biological effect was found with AsBe, a major arsenic compound contained in large quantities in the various marine animals ingested daily as seafood in many countries.…”
Section: à3mentioning
confidence: 88%
See 1 more Smart Citation
“…5,6 It was reported that AsCho had a weak, but significant, in vivo acute toxicity in mice, 7 but we recently demonstrated that AsCho had no in vitro cytolethality on cultured mouse splenocytes, thymocytes, Peyer's patch lymphocytes, macrophages and bone marrow cells. 1,8,9 In this study, we examined whether AsCho has any in vivo immunotoxicity, and found that it was slightly, but significantly, immunotoxic in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…7 In contrast, we recently observed that AsCho did not show any cytolethality in cultured mouse immune effector cells, such as macrophages, splenocytes, thymocytes, Peyer's patch lymphocytes and bone marrow cells, in vitro. 1,8,9 In this study, we examined whether AsCho has any in vivo immunological effects using mouse models, and found that AsCho had weak immunotoxicity when administered orally.…”
Section: Introductionmentioning
confidence: 99%